Electrifying the disk: a modular rotating platform for wireless power and data transmission for Lab on a disk application1. Issue 12 (21st June 2015) - Höfflin, Jens; Torres Delgado, Saraí M.; Suárez Sandoval, Fralett; Korvink, Jan G.; Mager, Dario
<x xml:space="preserve">Abstract</x> We present a design for wireless power transfer, via inductively coupled coils, to a spinning disk. This is an important demonstration of what we believe will have numerous applications in the future.